Prática de análise linguística: um olhar sobre as atividades da coleção português: conexão e uso - Regner, Ana Paula (2024)
This research aims to investigate the Linguistic Analysis (LA) activities proposed in the textbook (DL) Português: conexão e uso of the 6th year of Elementary School, to verify to what extent they contribute to the practice of Text Production under a textual/discursive genres perspective. To this end, we delimited the following specific objectives: i) describe the skills of AL/Semiotics and Text Production based on the lexico-grammatical categories of the transitivity system, of Systemic-Functional Grammar (SFG); ii) analyze the didactic activities of LA and Text Production in terms of nature, levels of complexity, objects of knowledge and language strata; iii) verify whether the processes, objects of knowledge and learning contexts proposed in the skills are effectively covered in the activities and iv) discuss to what extent the LA activities proposed in the textbook promote an effective articulation between LA and Text Production. The research, developed from the qualitative approach of an interpretivist nature (ALAMI; DESJEUX; GARABUAU-MOUSSAOUI, 2010), presents as corpora the skills of LA/Semiotics and Text Production from the National Common Core Curriculum (BNCC) along with the activities of these two language practices present in units 1 and 2, sections Leitura 1 and subsections of Exploração de Texto, Recursos Expressivos, Cultura Digital, A lingua não é sempre a mesma and Produção Escrita of the textbook. The theoretical-methodological contribution consists of the resumption of the educational scenario of the 1980s (ANGELO, 1990; NEVES, 1990, 1993; TRAVAGLIA, 1996; HILA, 1998, SOARES 2002), in the consolidation of the term Practice of Linguistic Analysis (PAL) (GERALDI, 1984), in the guidelines provided by teaching documents (BRASIL, 1998, 2018) and views from other researchers on how PAL has been recontextualized in textbooks. Furthermore, we discuss the concepts of Systemic-Functional Linguistics (SFL) (HALLIDAY, 1985; HALLIDAY; MATTHIESSEN, 2014), especially the language strata and the transitivity system that are our analysis tools. The results of the analysis reveal that the skills are mainly composed of cognitive mental processes, followed by creative material processes that refer to the contents that must be worked on and the predominance of circumstances of place, manner and purpose that present the contexts and specifications of learning. These processes, objects of knowledge and learning contexts, are partially covered by the units' LA and Text Production activities. Among them, unit 2 is the one that presents a proposal closest to working with the complaint letter from a textual/discursive genres perspective because LA activities promote an articulation with Text Production activities regarding cognitive processes and levels of complexity and objects of knowledge. In unit 1, when focusing on the fictional narrative, the articulation between activities occurs only in relation to cognitive processes and levels of complexity. In this way, the identification of gaps in what involves the objects of knowledge (unit 1) and language strata (units 1 and 2) signals a textual/discursive perspective under construction in the investigated collection.